European Graduate School in Addiction Research: A contribution to the research education of PhD/MD students in Europe. (2nd November 2017) - Forberger, Sarah; Riedel, Oliver; Bühringer, Gerhard
Abstract: This paper reports on the European Graduate School in Addiction Research (ESADD), which contributes to the scientific education of PhD/MD addiction research students and promotes interdisciplinary cooperation and academic networking in Europe. ESADD is a two-year course, built first from a conceptual analysis of knowledge needs, then iteratively refined based on practical experiences. Its major components are six seminar weeks, homework assignments and an internship in a foreign research group. As part of an internal quality management system, comprehensive evaluations of the programme took into account goals and objectives of the seminar weeks, workloads, study materials, relevance and usefulness of acquired skills, and organisational issues. Assessments of lecturers evaluated their teaching performance and the relevance of their topics. Forty-two out of 45 participants from all over Europe completed one of the three courses carried out between 2008 and 2015. All reported that ESADD provided them with a broad overview of knowledge in the field, and 41 participants were satisfied with the quality of the seminar weeks. ESADD thus seems to be an effective way to educate PhD students from different research disciplines and to provide a comprehensive body of scientific knowledge and competencies on addiction-related research topics. Further ESADD enriches the higher education landscape in addiction education.